2009
DOI: 10.1097/icl.0b013e3181998dec
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Case of Microcysts Associated With Silicone Hydrogel Contact Lens: Findings on In Vivo Confocal Laser Microscopy

Abstract: Microcysts may occur in persons who wear silicone hydrogel CLs caused by inflammatory, mechanical etiology, or a toxic reaction from the solution/lens interaction that the patient was using. In vivo Confocal laser microscope is useful for making a definite diagnosis of microcysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Several other protein synthesis inhibitors tested show amoebicidal properties but have limited cysticidal effects. These include prednisolone (irreversibly binds with glucocorticoid receptors, inhibiting gene transcription for cytochrome oxidase 2 , cytokines, cell adhesion molecules, and inducible NO synthase) (52), beta-methasone phosphate (binds to plasma transcortin and becomes active when it is not bound to transcortin) (81), and linezolid (inhibits the formation of subunits of ribosome) (39,41,50,51,71,72).…”
Section: Protein Synthesis-inhibiting Drugsmentioning
confidence: 99%
“…Several other protein synthesis inhibitors tested show amoebicidal properties but have limited cysticidal effects. These include prednisolone (irreversibly binds with glucocorticoid receptors, inhibiting gene transcription for cytochrome oxidase 2 , cytokines, cell adhesion molecules, and inducible NO synthase) (52), beta-methasone phosphate (binds to plasma transcortin and becomes active when it is not bound to transcortin) (81), and linezolid (inhibits the formation of subunits of ribosome) (39,41,50,51,71,72).…”
Section: Protein Synthesis-inhibiting Drugsmentioning
confidence: 99%
“…Toshida and Muakami 18 reported an atypical case of microcysts associated with silicone hydrogel contact lens wear based on observations with an in vivo confocal laser microscope. They reported that treatment with betamethasone phosphate and levofloxacin eye drops (both five times daily) resulted in alleviation of the condition after 10 days.…”
mentioning
confidence: 99%